Factors Affecting Knowledge Sharing Behavior in The Virtual Teacher Community “Duta Rumah Belajar” - Devialina Puspita; Aida Vitayala Hubeis; Pudji Muljono (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to examine the relationship between social capital variables (social ties, social trust, and shared vision), individual motivation (self-efficacy, Altruism, and reciprocal norms), and technology (perceived ease of use and enjoyment of participation). On knowledge sharing intention variable, knowledge sharing intention variable on knowledge sharing behavior, and the relationship between individual characteristics and all variables. This study involved 128 respondents from the online community Duta Rumah Belajar who are outstanding teachers representing 34 provinces in Indonesia who PUSDATIN strictly selected, the Ministry of Education and Culture to promote the Rumah Belajar portal). Data analysis used the Chi-Square method and the Structural Equation Model Partial Least Square (SEM PLS). The results showed that individual motivation had a significant effect on knowledge-sharing intentions. Social capital and technology had no significant impact on knowledge sharing intentions. Knowledge sharing intentions had a substantial effect on knowledge sharing behavior, and there were no differences in individual characteristics of all research variables.